Penetapatan Metode Ekstraksi Fosfor dan Kalium untuk Tanaman Cabai pada Tanah Andisol - Dermawan, Rahmansyah Dermawan; Anas Dinurrohman Susila; Purwono; Budi Nugroho; Sugiyanta (Jurnal Hortikultura Indonesia, 2022)
Determination of the P and K-soil extraction method on Andisols for chili cultivation is an important step in formulating fertilizer recommendations. The research was conducted in the plastic house of the PKHT Experimental Farm IPB, Tajur, Bogor at position 6038’12.9”S 106049’25.2.9”E and 388 m above sea level. The soil sample came from Cikajang Village, Garut Regency at position 7021’46.7”S 107045’13.1”E. Soil tests were carried out at the Chemistry and Soil Fertility Laboratory, Faculty of Agriculture, IPB. The study was arranged based on a randomized complete block design with 1 factor, namely Andisols and repeated in five replications. The parameter observed was the correlation between five extraction methods of P and K-soil (Mechlich-1, Bray-1, Morgan-Wolf, Ammonium acetate, and HCl-25%) and the relative dry weight of biomass of chili plants. The results showed that there were differences in the correlation between the P and K extraction methods and the relative dry weight of chili plants. The Morgan-Wolf showed the best correlation in extracting P-Andisols (r=0.94) while in the K-Andisols correlation test, the Ammonium acetate showed the best results (r=0.97). The Mechlich-1 can be used as an alternative extraction method for P and K-soil Andisol for chili plants. Keywords: Ammonium acetate, coefficient correlation, Morgan-Wolf, soil test, vegetables